ATRIBUTOS DO SOLO E PRODUÇÃO DE Urochloa brizantha cv. Marandu NO DISTRITO DE JASY CAÑY, PARAGUAI - COLMÁN RIBELATTO, PATRICIA JUANA (2017)
Milk production is one of the most important activities in the Paraguayan economy, however in most cases this activity is being developed under degraded pastures due to lack of management which over time can affect soil chemical and physical quality and, therefore, the sustainability of animal production. The objective of this work was to characterize the physical and chemical attributes of soils under Marandu grass and determine their productivity using different fertilizations. The study was conducted in 4 areas located in the district of Jasy Cañy-Canindeyú, Paraguay. In order to evaluate the chemical attributes, soil samples were collected before fertilization in the 0-10 cm and 10-20 cm layers, using the levels of Ca2+, Mg2+, K+, extractable P, base saturation, aluminum saturation, exchangeable acidity, Al3+, CTCpH7,0, pHCaCl2 and organic matter as chemical indicators of soil quality. For the physical attributes, soil samples were collected in the 0-5 cm, 5-10 cm and 10-15 cm layers and soil total porosity, macro and microporosity, porosity in the macropore domain, water storage capacity and air storage capacity, soil particle size and resistance to root penetration were determined. For dry matter production and height of the pasture, a complete randomized block design was used and the treatments consisted of control (without fertilization), nitrogen fertilization (100 kg ha-1) and fertilization with N-P2O5-K2O (100-4080 Kg ha-1), the sampling were carried out periodically between summer and winter. Based on the results the soils present a medium acidity, with no Al3+ toxicity, good base saturation, low MO and CTCpH 7.0, lack of Ca2+, K+ and extractable P and high Mg2+ content in relation to Ca2+. The physical attributes indicated that the soils of the studied areas do not present physical restrictions to plant growth, except for the area 4 that presented low levels of macroporosity. Fertilization with N and N-P2O5-K2O provided significant increases in dry matter yield and height of Marandu grass presenting high responsive capacity, and it is possible to conclude that fertilization is the fundamental factor for pasture productivity.